Variations in branching pattern of renal artery and arrangement of hilar structures in the left kidney: clinical correlations, a case report - Verma, Poonam; Arora, Anterpreet K.; Sharma, Punita; Mahajan, Anupama (Italian Journal of Anatomy and Embryology, 2012)
Traditionally, anatomy textbooks describe each kidney to receive irrigation from a single renal artery. However, current literature reports great variability in renal blood supply, the number of renal arteries and the arrangement of hilar structures on the left side. Here a case is described where, on the right side, the renal artery had its origin from the abdominal aorta, as normally occurs, and followed a normal course and relations in the hilum. There were three renal arteries on the left side. The left main renal artery took origin from the anterior aspect of the abdominal aorta. The other two arteries took their origin from a common trunk coming out of the lateral aspect of abdominal aorta inferior to the main left renal artery. The renal vein at the hilum was found between the main renal artery and the ventral branch of the common trunk, anteriorly, and the dorsal branch of the common trunk, posteriorly. Such variation has great implications when surgery is indicated, as in renal transplants, urological and radiological procedures, reno-vascular hypertension, renal trauma and hydronephrosis. As the number of renal surgical and radiological interventions increase, a better understanding of the anatomy of renal arteries and their branches gain importance. To plan the adequate surgical procedure and to avoid any vascular complication, Multi Detector Computer Tomography (MDCT), angiography and arteriography should be performed prior to surgery (nephrectomy).